Carbon-based catalyst with high active oxygen functional group and application thereof
By developing a carbon-based catalyst with high reactive oxygen functional groups in electrochemical strategies, the problems of slow kinetics and low selectivity of 2e-ORR in electrochemical strategies were solved, and efficient, safe and green electrocatalytic synthesis of hydrogen peroxide was achieved.
Patent Information
- Application Number
- CN202411838256.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art When hydrogen peroxide (H2O2) is produced by double-electron oxygen reduction reaction (2e-ORR) in electrochemical strategies, the kinetics are slow and the selectivity is low, and the precious metal catalysts are costly and scarce.
A carbon-based catalyst CB-85-6h with high reactive oxygen functional groups was developed, prepared by a water-phase thermal synthesis method with stirring at 85°C for 6 hours, and combined with a three-electrode system to achieve high selectivity and yield in the electrocatalytic synthesis of hydrogen peroxide.
The high selectivity (90.1%) and ultra-high yield (3302.23mmol gcat.-1h-1) of H2O2 are achieved, reducing the cost and environmental impact of the catalyst, while combining it with renewable energy, which is safe, green and environmentally friendly.
Smart Images

Figure CN119876998A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrocatalysis, in particular to a carbon-based catalyst with highly active oxygen functional groups and applications thereof. Background Art
[0002] Hydrogen peroxide (H2O2) is a high-value, environmentally friendly oxidant with a wide range of applications in chemical synthesis, papermaking, pulping, wastewater treatment, and other fields. Currently, the production of H2O2 mainly relies on the industrial anthraquinone oxidation process, which is energy-intensive and resource-intensive, and produces many harmful byproducts in the cascade reaction. In recent years, electrochemical strategies through the two-electron oxygen reduction reaction (2e-ORR) pathway have provided an attractive route to produce H2O2 that is portable and safe. However, due to the competing four-electron (4e-) pathway, the core ORR usually has slow kinetics and low selectivity. Therefore, in order to trigger the two-electron pathway and suppress the subsequent four-electron step to achieve efficient electrosynthesis of H2O2, it is necessary to rationally design catalysts with high activity, selectivity, and stability. Noble metals and their alloys (such as Pt-Hg, Pd-Hg, Au-Pd) are currently recognized as efficient 2e-ORR catalysts with small overpotentials and high selectivity, but their large-scale application is limited due to their high cost and scarcity. Summary of the invention
[0003] The purpose of the present invention is to develop a carbon-based catalyst with highly active oxygen functional groups, which is simple to prepare and convenient to use, and a synthesis method and application thereof.
[0004] To achieve the purpose of the present invention, the present invention discloses a carbon-based catalyst with highly active oxygen functional groups: the carbon-based catalyst is named CB-85-stirring time, where 85 is the synthesis temperature, and the H2O2 selectivity of the prepared carbon-based catalyst reaches 90.1%, and the H2O2 yield in the process of electrocatalytic synthesis of hydrogen peroxide in a three-electrode system reaches 3302.23mmol g cat. -1 h -1 .
[0005] Further, the synthesis method is as follows:
[0006] First, 50-100 mg of original carbon black is dispersed in 50-100 mL of deionized water, and the mixture is dispersed in ultrasound for 1-1.5 hours; then it is stirred at 85° C. for 4-8 hours; the obtained product is centrifuged and dried in a vacuum oven at 60-65° C. for 8-12 hours.
[0007] Furthermore, the original carbon black is Cabot Vulcan XC-72.
[0008] Furthermore, the raw carbon black is firstly pretreated with nitric acid.
[0009] Furthermore, the carbon-based catalyst with the best catalytic effect was obtained by stirring at 85°C for 6 hours.
[0010] The above-mentioned carbon-based catalyst with highly active oxygen functional groups is used for electrocatalytic synthesis of hydrogen peroxide.
[0011] Furthermore, a three-electrode system is used to realize the electrocatalytic synthesis of hydrogen peroxide, including dispersing catalyst powder in a mixed solution containing ethanol and 5% Nafion solution, and then obtaining a uniform catalyst suspension by ultrasound, dropping the suspension on carbon paper and vacuum drying to prepare a working electrode, a platinum mesh as a counter electrode, and a mercury oxide electrode as a reference electrode, in an H-type cell separated by a Nafion115 membrane, under the condition of O2 saturation of 0.1M KOH, the scanning rate is 10mV / s, the rotation speed is 1600rpm, and the ORR polarization curve is collected by linear sweep voltammetry in the range of 0.0-1.0Vvs.RHE.
[0012] Furthermore, in order to detect the generated H2O2, the Pt ring potential was maintained at 1.5 V vs. RHE during the LSV process.
[0013] Furthermore, before the ORR measurement, the RRDE was subjected to a scanning cyclic voltammetry curve pre-activation process at a scanning rate of 50 mV / s, and the RRDE was electrochemically cleaned until a stable CV curve was obtained.
[0014] Carbon-based metal-free materials have the advantages of low cost, high abundance and flexible and adjustable structure, and are more promising electrocatalysts for the production of H2O2. The introduction of a variety of oxygen-containing functional groups into carbon-based catalysts using strong oxidation methods is helpful for the electrochemical synthesis of hydrogen peroxide, because it only uses O2 and water as raw materials and can be combined with renewable energy. It has the advantages of safety, greenness, environmental protection, and strong on-site production capacity. We propose a mild and simple aqueous phase thermal synthesis method to enhance the highly active oxygen functional groups on the surface of carbon materials. The prepared catalyst has good H2O2 selectivity (90.1%) and ultra-high H2O2 yield (3302.23mmol g cat. -1 h -1 ), in order to develop high 2e - This provides new ideas for practical carbon-based catalysts with ORR catalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The detailed description given as non-limiting examples better explains what the invention consists of and how it can be implemented, and furthermore, refers to the accompanying drawings, in which:
[0016] Figure 1 In the figure, a is a schematic diagram of the synthesis of material CB-85-6h; be is a scanning electron microscope image of CB, CB-85-4h, CB-85-6h and CB-85-8h; f is a TEM image of CB-85-6h, and the inset is the corresponding high-magnification image; g is the EDS spectrum of CB-85-6h.
[0017] Figure 2 In the figure, a is the CV curve of CB-85-6h tested in Ar and O2 saturated electrolyte (0.1M KOH). b is the H2O2 yield of the catalyst under different synthesis temperature conditions; c is the H2O2 yield of the catalyst under different synthesis time conditions; d is the LSV curve of the catalyst on RRDE in O2 saturated 0.1M KOH under different synthesis time conditions, calculated by LSV curve; e is H2O2 selectivity; f is the number of electron transfers; g is the H2O2 yield of CB-85-6h under different catalyst loadings; h is the H2O2 yield of CB-85-6h under different potentials; i is the comparison of CB-85-6h catalyst with catalysts reported in the literature.
[0018] Figure 3 a is the scanning rate of 10 mV s -1 a is the LSV curve at a rotation speed of 400-2025 rpm; b is the KL diagram of the LSV curve at different electrode potentials; c is the selectivity of H2O2 of CB-85-6h at different potentials.
[0019] Figure 4 Comparison of H2O2 yields of Ar-CB-85-6h and CB-85-6h.
[0020] Figure 5 a is the XRD pattern of CB, CB-85-4h, CB-85-6h and CB-85-8h; b is the Raman spectrum of carbon-based catalysts under different temperature conditions; c is the Raman spectrum of CB, CB-85-4h, CB-85-6h and CB-85-8h; d is the N2 adsorption-desorption isotherm of CB and CB-85-6h; e. XPS total spectrum; f. C1s spectrum; g. O1s spectrum and h. the relative proportion of oxygen-containing functional groups in different materials; i. the water contact angle of CB and CB-85-6h.
[0021] Figure 6 a is the LSV curve (scan rate 20 mV s) tested in N2-saturated 0.1 M KOH electrolyte containing 10 mM K3Fe(CN)6 -1 , E ring =1.55 V vs. RHE); b is the linear fit of the diffusion-limited current density recorded on the ring-disk electrode at different rotation speeds, and the collection efficiency is the ratio of the absolute value of the ring current to the absolute value of the disk current.
[0022] Figure 7 a. XPS total spectrum, b. C1s spectrum, c. O1s spectrum of catalyst Ar-CB-85-6h synthesized under Ar conditions, d. Comparison of oxygen functional group content of different materials.
[0023] Figure 8 a is the relationship between the capacitance current and the scan rate of different materials; b is the Tafel diagram of different materials; c is the electrochemical impedance spectrum (EIS) comparing different materials; d is the experiment of CB-85-6h cycling 5 times at 0.2Vvs.RHE; e is the current measurement curve of CB-85-6h at 0.2Vvs.RHE for 36h and the linear fitting curve of the change in H2O2 concentration; f is the degradation efficiency of organic dye MB over time, and the inset is a photo of the MB solution after adding the cathode electrolyte during the degradation process. DETAILED DESCRIPTION
[0024] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0025] Synthesis of carbon-based catalysts
[0026] First, 50 mg of original carbon black (CB, Cabot Vulcan XC-72) was dispersed in a 250 mL round-bottom flask filled with 50 mL of deionized water, and the mixture was dispersed in ultrasound for 1 h, and then stirred at 85 ° C for 4, 6, and 8 h, respectively, to obtain carbon-based catalysts synthesized at different times; finally, the obtained product was centrifuged and dried in a vacuum oven at 60 ° C overnight. The obtained carbon-based catalyst is named CB-85-stirring time, for example: under the conditions of 85 ° C and stirring time of 6 h, it is defined as CB-85-6h.
[0027] In addition, the dried carbon-based catalyst was heated at 85°C in an Ar atmosphere and stirred for 4-8 h to synthesize other catalysts for comparison.
[0028] The carbon-based catalysts prepared above with different stirring times were subjected to subsequent experimental measurements.
[0029] like Figure 1 As shown in ag, Figure 1 a. Schematic diagram of the synthesis of material CB-85-6h. b. SEM images of CB, CB-85-4h, CB-85-6h and CB-85-8h. f. TEM image of CB-85-6h. The inset is the corresponding high-magnification image. g. EDS spectrum of CB-85-6h.
[0030] Figure 1a is a schematic diagram of the synthesis of the material. After carbon black was pretreated with nitric acid, the material was thermally synthesized at 85°C in water. We characterized the structure of the synthesized material by first Figure 1 The scanning electron microscope (SEM) images in be show that after functionalization treatment for different time periods, the carbon black structure has not changed much and is all irregular spherical particles, indicating that the morphological changes under mild oxidation treatment are negligible. TEM images ( Figure 1 f) The irregular spherical morphology of carbon black can also be seen. The uniform distribution of elements C, N and O in the sample was confirmed by energy dispersive X-ray (EDS) spectroscopy ( Figure 1 g).
[0031] Electrochemical measurements
[0032] The electrocatalytic activity evaluation was carried out on an electrochemical workstation (CHI-760E) using a three-electrode system, including a rotating ring disk electrode (RRDE) as the working electrode, a platinum mesh as the counter electrode, and a mercury oxide electrode (Hg / HgO) as the reference electrode in an O2-saturated 0.1M KOH electrolyte.
[0033] In the experiment, 3 mg of carbon-based catalyst powder was dispersed in a mixed solution containing ethanol (950 μL) and 5% Nafion (50 μL) solution, and then a uniform carbon-based catalyst suspension was obtained by ultrasound. The suspension was dropped on carbon paper and vacuum dried to prepare a working electrode.
[0034] Before ORR measurement, the RRDE was subjected to a scanning cyclic voltammetry (CV) pre-activation process (scan rate of 50 mV / s) and electrochemically cleaned until a stable CV curve was obtained. ORR polarization curves were collected by linear sweep voltammetry (LSV) in the range of 0.0 to 1.0 V vs. RHE under O2 saturation conditions of 0.1 M KOH at a scan rate of 10 mV / s and a rotation speed of 1600 rpm. In order to detect the generated H2O2, the Pt ring potential was kept at 1.5 V vs. RHE during the LSV process.
[0035] All potentials in this system are calibrated to reversible hydrogen electrode potentials using the following formula.
[0036] E(vs.RHE)=E(vs.Hg / HgO)+0.059pH+0.098
[0037] According to the disk current (I d ) and the ring current (I r ) The results determine the H2O2 selectivity (H2O2%) and the number of transferred electrons (n), the formula is as follows:
[0038]
[0039] In the formula, I disk is the disk current, I ring is the ring current, and the collection efficiency N of RRDE is determined to be 0.34, such as Figure 6 As shown in ab, Figure 6 a. LSV curves measured in N2-saturated 0.1M KOH electrolyte containing 10 mM K3Fe(CN)6 (scan rate 20 mV s -1 , E ring =1.55Vvs.RHE) Figure 6 b. Linear fit of the diffusion-limited current density recorded on the ring-disk electrode at different rotation speeds. The collection efficiency is the ratio of the absolute value of the ring current to the absolute value of the disk current.
[0040] In addition to the above RRDE method, the rotating disk electrode (RDE, the disk geometric area is 0.19625cm 2 ) to calculate the electron transfer number (n), such as Figure 3 As shown in ac, Figure 3 a is the scanning rate of 10 mV s -1 , LSV curve when the speed is 400~2025rpm; Figure 3 b is the KL diagram of LSV curve at different electrode potentials; Figure 3 c is the selectivity of H2O2 of CB-85-6h at different potentials;
[0041] The electrode speed of RDE was fixed at 400, 625, 900, 1225, 1600 and 2025 rpm for Koutecky-Levich analysis to calculate the electron transfer number (n):
[0042]
[0043] where j and j k They are the current density and dynamic current density (mA cm -2 ), ω is the angular velocity (rpm), and F is the Faraday constant (96485C mol -1 ), is the O2 concentration (1.2×10 -6 mol cm -3 ), The diffusion coefficient of O2 is 1.9×10 -5 cm 2 s -1 ), ν defines the kinematic viscosity of O2 (1×10 -2 cm 2 s -1 ).
[0044] The selectivity of H2O2 in the ORR process is calculated by the following formula:
[0045]
[0046] Electrochemical performance test
[0047] Figure 2 middle:
[0048] a. CV curve of CB-85-6h tested in Ar and O2 saturated electrolyte (0.1MKOH). b. H2O2 yield of carbon-based catalyst under different synthesis temperature conditions. c. H2O2 yield of carbon-based catalyst under different synthesis time conditions. d LSV curve of carbon-based catalyst on RRDE in O2 saturated 0.1MKOH under different synthesis time conditions. e. H2O2 selectivity and f. electron transfer number were calculated by LSV curve. g. H2O2 yield of CB-85-6h under different carbon-based catalyst loadings. h. H2O2 yield of CB-85-6h at different potentials. i. Comparison of CB-85-6h carbon-based catalyst with carbon-based catalysts reported in literature.
[0049] The CB-85-6h carbon-based catalyst was dropped on carbon paper as the working electrode to evaluate its 2e - ORR performance. The corresponding experiments were carried out in an H-type cell separated by Nafion115 membrane with a platinum mesh as the counter electrode and Hg / HgO as the reference electrode under 0.1M KOH solution as the environmental condition. 4+ The generation of H2O2 was determined spectrophotometrically, and the corresponding calibration curve is shown in Figure S4. Figure 2 a shows the CV curves of the carbon-based catalyst in Ar- and O2-saturated electrolytes, respectively. It can be clearly seen that the carbon-based catalyst has an obvious cathode reduction peak in the O2-saturated electrolyte, but almost none in the Ar-saturated electrolyte, proving that the material has the ability to catalyze oxygen reduction. Figure 2 It can be concluded that the catalytic performance of the carbon-based catalyst is best when the temperature is 85 °C and the reaction time is 6 h, and the performance of the CB-85-6h carbon-based catalyst synthesized under Ar conditions is average ( Figure 4 ), confirming the importance of oxygen in the material synthesis process. Therefore, CB, CB-85-4h, CB-85-6h and CB-85-8h carbon-based catalysts were selected for the study of electrochemical catalytic performance.
[0050] The carbon-based catalysts CB, CB-85-4h, CB-85-6h and CB-85-8h were firstly tested for 2e - Electrocatalytic performance for ORR, with a collection efficiency of 34% ( Figure 6 , Supporting Information). Figure 2 d shows the linear sweep voltammetry (LSV) curve of the ORR process tested at 1600 rpm and the H2O2 current density tested on the Pt ring electrode at a constant potential of 1.50 V vs. RHE. The ORR activity of CB-85-6h is significantly better than that of other carbon-based catalysts, and its current density on the ring electrode is larger. The calculated H2O2 selectivity and electron transfer number (n) change with potential are shown in Figure 2. Figure 2 In the wide potential range of 0.0-0.60 V, the H2O2 selectivity of the CB-85-6h carbon-based catalyst is greater than 80% (with a maximum of 90.1%), and n is less than 2.4, indicating that the carbon-based catalyst has high selectivity. - ORR pathway. In contrast, CB exhibited lower H2O2 selectivity and higher n value, which indicated the importance of highly active oxygen functional groups in adjusting ORR selectivity. In addition, the linear sweep voltammetry curves ( Figure 3 ) further indicates that its main 2e - The ORR process produces H2O2. Figure 2 gh, when the loading amount is 0.1 mg cm -2 , CB-85-6h obtained the highest yield at a potential of 0.2 V vs. RHE, further comparing the carbon-based catalysts with other recently reported electro-carbon-based catalysts ( Figure 2 i, Table 2), the results clearly show that the performance of CB-85-6h carbon-based catalyst is better than other carbon-based catalysts.
[0051] Figure 5 a. XRD patterns of CB, CB-85-4h, CB-85-6h and CB-85-8h. b. Raman spectra of carbon-based catalysts under different temperature conditions. c. Raman spectra of CB, CB-85-4h, CB-85-6h and CB-85-8h. d. N2 adsorption-desorption isotherms of CB and CB-85-6h. e. XPS total spectrum. f. C1s spectrum. g. O1s spectrum and h. Relative proportions of oxygen-containing functional groups in different materials. i. Water contact angles of CB and CB-85-6h.
[0052] The X-ray diffraction (XRD) diagram shows that the material has two broad peaks at 23.5° and 44°, belonging to the 002 and 100 diffraction modes respectively. All materials have the characteristics of disordered carbonaceous structure ( Figure 5 a). This can be further confirmed by Raman spectroscopy ( Figure 5 bc), located at 1350cm -1The peak (D peak) is related to disordered or defective carbon structure, 1590cm -1 The peak at (G peak) belongs to the sp 2 The D peak intensity of all materials is higher than the G peak intensity, indicating that defects and disordered carbon exist in the synthesized materials. D / I G The smallest ratio indicates that the material has the highest degree of graphitization, which is more conducive to 2e - ORR pathway. Figure 5 d is the N2 adsorption-desorption isotherm of the carbon-based catalyst. The isotherm is a typical type IV isotherm with an obvious hysteresis loop, indicating that the materials all have mesopores. According to previous reports, the mesoporous structure is conducive to the generation activity of H2O2. The BET surface area of CB is 388.29 m 2 g -1 , which is less than 398.06m of CB-85-6h 2 g -1 , indicating that the specific surface area of the material increases after oxidation, which is more conducive to catalytic reaction. XPS (X-ray photoelectron spectroscopy) was used to analyze the chemical valence state of the elements on the surface of the carbon-based catalyst. Figure 5 e is the full spectrum of XPS of four carbon-based catalysts. It can be seen from the figure that the material is mainly composed of C and O elements. The type and distribution of oxygen functional groups of the samples are quantified by further peak fitting. Figure 5 f shows the C1s spectra of the four materials. The C1s spectrum of the CB-85-6h carbon-based catalyst can be obtained by fitting the sp 2 Carbon (C=C) at 284.7 eV, sp 3 Carbon is at 285.2eV, carbon oxygen single bond (CO) is at 286.2eV, carbon oxygen double bond (C=O) is at 287.6eV, carboxyl group (O=CO) is at 290.2eV. At the same time, high-resolution O1s spectrum ( Figure 5 g) can be fitted into three peaks at 532eV, 533.1eV and 533.9eV, which are respectively attributed to C=O, COC / COOH and CO(H) groups. By calculating the fitting peak area corresponding to O1s, the relative proportions of the oxygen-containing functional groups of these four materials are obtained ( Figure 5 h), the data clearly show that after functionalization under specific conditions, the relative proportion of C=O functional groups increased significantly, and the relative proportion of CO(H) functional groups decreased. Under different conditions, the relative proportions of functional groups changed slightly. Among them, the relative proportion of C=O in material CB-85-6h was the highest (41.63%), and the ratio of COC / COOH was also relatively high, indicating that the high activity of the material in generating H2O2 may be due to the increase of these active functional groups. Figure 5The comparison of water contact angles shows that the hydrophilicity of the oxidized material decreases. This is because the -OH functional groups with strong hydrophilicity are greatly reduced after oxidation, which can also be verified by XPS results. The reduction in hydrophilicity is beneficial to the adsorption of O2 by the carbon-based catalyst, which is beneficial to the oxygen reduction reaction. In addition, we conducted XPS tests on the carbon-based catalyst Ar-CB-85-6h synthesized under Ar conditions ( Figure 7 ), it can be seen that it is not much different from the original carbon black, which shows that the oxygen in the air plays a vital role in the synthesis process, which can promote the formation of active functional groups such as C=O, and is more conducive to improving the activity of the material.
[0053] Figure 7 a. XPS total spectrum, b. C1s spectrum, c. O1s spectrum of catalyst Ar-CB-85-6h synthesized under Ar conditions, d. Comparison of oxygen functional group content of different materials.
[0054] Hydrogen peroxide concentration determination
[0055] The concentration of hydrogen peroxide was determined in an H-type electrolytic cell separated by a Nafion 115 membrane. The two electrolytic chambers were filled with 30 mL of 0.1 mol L -1 KOH solution. Carbon paper (Toray, TGP-H-060, 1.0 cm × 1.0 cm) loaded with CB-85-6h carbon-based catalyst suspension was used as the working electrode. First, 3 mg CB-85-6h was dispersed in a mixture containing ethanol (950 μL) and 5% Nafion (50 μL) solution, and then ultrasonicated for 20 min by an ultrasonic cleaner to obtain a uniform carbon-based catalyst suspension. Finally, 50 μL of the above suspension was dropped on the carbon paper and vacuum dried to prepare the working electrode. The cerium sulfate method was used to determine the H2O2 yield. The reaction principle is: 2Ce 4+ +H2O2→2Ce 3+ +2H + +O2, and the Ce before and after the reaction was determined by UV-visible spectroscopy. 4+ The maximum wavelength of the measurement is 320nm. According to the absorbance of cerium sulfate solution at 320nm and Ce 4+ The linear relationship of the concentration (0.02-0.18 mM) is used to obtain a standard curve, through which the concentration of H2O2 in the sample can be obtained.
[0056] Calculation of H2O2 yield
[0057] The formula for calculating the yield of H2O2 is as follows:
[0058]
[0059] Where V(L) is the extracted cathode solution and Ce 4+The total volume of the solution; C0 and C x (mol L -1 ) is Ce before and after adding generated H2O2 4+ The concentration of the solution; V0(L) is the initial Ce 4+ The volume of the solution, V X (L) Ce is added to the cathode solution 4+ m is the mass of the carbon-based catalyst on the carbon paper, t is the electrolysis time, and 30 (mL) is the volume of the solution in the cathode electrolysis chamber.
[0060] Figure 8 a. Relationship between capacitance current and scan rate of different materials. b. Tafel plots of different materials. c. Comparison of electrochemical impedance spectra (EIS) of different materials. d. CB-85-6h cycled 5 times at 0.2V vs. RHE. e. Current measurement curve of CB-85-6h at 0.2V vs. RHE for 36h and linear fitting curve of H2O2 concentration change. f. Degradation efficiency of organic dye MB over time, the inset is a photo of MB solution after adding cathode electrolyte during degradation.
[0061] The electrochemical active area (ECSA) was measured in 0.1M KOH alkaline electrolyte at a scan rate of 40 to 180 mV / s in the voltage range of 0.70 to 0.80 V vs. RHE. After normalization, the electrochemical capacitance value C dl (CB-85-6h) is 0.741mF cm -2 , while C dl (CB) is 0.175mF cm -2 ( Figure 8 a), it can be seen that the specific surface area is increased compared with that before oxidation treatment, which indicates that mild oxidation heat treatment helps to increase the specific surface area, thus facilitating the exposure of active sites. The Tafel slope can confirm the fast kinetics of the ORR reaction. Figure 8 As shown in b, the Tafel slopes of CB-85-4h, CB-85-6h, and CB-85-8h are 149.80, 142.1, and 148.04 mV dec, respectively. -1 , much lower than CB (173.25mVdec -1 Among them, CB-85-6h has the lowest Tafel slope, indicating that its ORR kinetics is faster. Figure 8 c) shows that CB-85-6h has better conductivity and catalytic activity because its charge transfer resistance is lower than that of other catalysts. Stability is another important parameter for evaluating catalyst performance. Therefore, we tested the ORR performance of CB-85-6h at 0.2 V for 5 consecutive cycles. Figure 8 As shown in Figure d, the H2O2 yield did not change much during the five cycle tests. In addition, the long-term stability test was carried out at a fixed potential of 0.2 V ( Figure 8 e) During the entire 36 h test period, the ORR current was quite stable, and the average increase rate of H2O2 concentration in the H-cell was 37.11 mg L -1 h -1 , the cumulative concentration of H2O2 reached 1.67 g L -1 To further demonstrate the use of catholyte for the removal of organic dyes via Fenton reaction, its capability in bleaching and water treatment processes was evaluated. Figure 8 As shown in Figure f, when cathode electrolyte is added to methylene blue, the color of methylene blue gradually becomes lighter with the increase of reaction time, and methylene blue is completely degraded within 1 hour, indicating that the H2O2 produced by this catalyst has potential industrial applications.
[0062] In summary, a carbon black-based catalyst with highly active oxygen functional groups can be prepared by simple aqueous phase heat treatment, and oxidation treatment can improve the activity and selectivity of carbon black in the generation of H2O2 during the ORR process. The selectivity of CB after oxidation is as high as 90.1%, and the H2O2 yield is as high as 3302.23mmol g cat. -1 h -1 The generated H2O2 can effectively degrade organic pollutants and has great application prospects. Through XPS characterization technology, we found that carbon-based catalysts with C=O groups have higher catalytic performance. Based on DFT calculations, we can attribute the origin of high activity to the COOH functional groups at the edge of graphene and the COC functional groups on the basal plane of graphene, revealing that different functional groups have different catalytic activity in 2e - These studies will provide insights into the active sites of ORR.
[0063] The above embodiments and illustrations do not limit the product form and style of the present invention. Any appropriate changes and modifications made by ordinary technicians in the relevant technical field should be deemed to be within the patent scope of the present invention.
Claims
1. A carbon-based catalyst having highly active oxygen functional groups, characterized in that: The carbon-based catalyst is named CB-85-stirring time, where 85 is the synthesis temperature. The H2O2 selectivity of the prepared carbon-based catalyst reaches 90.1%, and the H2O2 yield in the process of electrocatalytic synthesis of hydrogen peroxide in the three-electrode system reaches 3302.23mmol g cat. -1 h -1 .
2. A carbon-based catalyst having highly active oxygen functional groups as claimed in claim 1, characterized in that: The synthesis method is as follows: first, disperse 50 to 100 mg of original carbon black into 50 to 100 mL of deionized water, and disperse the mixture in ultrasound for 1 to 1.5 hours; then stir it at 85° C. for 4 to 8 hours; centrifuge the obtained product and dry it in a vacuum oven at 60 to 65° C. for 8 to 12 hours.
3. A carbon-based catalyst having highly active oxygen functional groups as claimed in claim 2, characterized in that: The original carbon black is Cabot Vulcan XC-72.
4. A carbon-based catalyst having highly active oxygen functional groups as claimed in claim 2, characterized in that: The raw carbon black is first pretreated with nitric acid.
5. A carbon-based catalyst having highly active oxygen functional groups as claimed in claim 2, characterized in that: The carbon-based catalyst with the best catalytic effect was obtained by stirring at 85°C for 6 hours.
6. Use of a carbon-based catalyst having a highly active oxygen functional group as claimed in any one of claims 1 to 5, characterized in that: Used for electrocatalytic synthesis of hydrogen peroxide.
7. The use of a carbon-based catalyst having a highly active oxygen functional group as claimed in claim 6, characterized in that: A three-electrode system is used to realize electrocatalytic synthesis of hydrogen peroxide, including dispersing catalyst powder in a mixed solution containing ethanol and 5% Nafion solution, then obtaining a uniform catalyst suspension by ultrasound, dropping the suspension on carbon paper and vacuum drying to prepare a working electrode, a platinum mesh as a counter electrode, a mercury oxide electrode as a reference electrode, and collecting ORR polarization curves by linear sweep voltammetry in an H-type cell separated by a Nafion115 membrane under O2 saturation conditions of 0.1M KOH at a scan rate of 10mV / s and a rotation speed of 1600rpm in the range of 0.0 to 1.0Vvs.RHE.
8. The use of a carbon-based catalyst having a highly active oxygen functional group as claimed in claim 7, characterized in that: To detect the generated H2O2, the Pt ring potential was kept at 1.5 V vs. RHE during the LSV process.
9. The use of a carbon-based catalyst having a highly active oxygen functional group as claimed in claim 7, characterized in that: Before the ORR measurement, the RRDE was subjected to a scanning cyclic voltammetry curve pre-activation process at a scanning rate of 50 mV / s, and the RRDE was electrochemically cleaned until a stable CV curve was obtained.